Palliative Curriculum Re-imagined: A Critical Evaluation of the UK Palliative Medicine Syllabus - Julian Abel; Allan Kellehear (Palliative Care, 2018)
The UK Palliative Medicine Syllabus is critically evaluated to assess its relationship and relevance to contemporary palliative care policy and direction. Three criteria are employed for this review: (1) relevance to non-cancer dying, ageing, caregivers, and bereaved populations; (2) uptake and adoption of well-being models of public health alongside traditional illness and disease models of clinical understanding; and (3) uptake and integration of public health insights and methodologies for social support. We conclude that the current syllabus falls dramatically short on all 3 criteria. Suggestions are made for future consultation and revision.